Digital activism in Southeast Asia: the #MilkTeaAlliance and prospects for social resistance - Putra, Bama Andika (Frontiers in Sociology, 2024)
Digital activism in Southeast Asia is on the rise. The Milk Tea Alliance, known as a collaboration of netizens voicing human rights concerns in Asia, has now reached the citizens of Southeast Asian autocratic regimes, including Myanmar. Having faced decades of human rights oppression and undemocratic rule, the Milk Tea Alliance of Myanmar has been vocal in disseminating the post-2021 military coup domestic situation and reimagining what a democratic Myanmar would consist of in the future. This perspective article argues the significance of digital activism for Myanmar by tracing what the existing literature misses in assessing this phenomenon and the nexus between Myanmar’s Milk Tea Alliance and the prospects of change in the state’s democratic landscape. Taking into consideration the development of digital activism in Myanmar between 2020 and 2024 and adopting the theoretical frameworks of “legislative opportunism” and “liberation technology,” this study concludes several possibilities: (1) the massive following of Myanmar’s Milk Tea Alliance could establish the foundations for offline movements mimicking the Arab Spring; (2) the harnessing of democratic thoughts among citizens; and (3) changes from within are feasible through digital activism compared to externally imposed actions such as through the regional organization of Southeast Asia, ASEAN.